PENINGKATAN KAPASITAS KWT SERUNI MELALUI PARTICIPATORY ACTION RESEARCH DALAM URBAN FARMING DAN HIDROPONIK - Solecha, Kusmayanti; Buani, Duwi Cahya Putri; Indriyani, Furi; Emiliana, Meutia Raissa; Apriliani, Resti Dhea Putri (Jurnal AbdiMas Nusa Mandiri, 2025)
This community service program aims to enhance the capacity and self-reliance of the Seruni Women Farmer Group (KWT Seruni) in supporting food security through training on urban farming and hydroponic cultivation, implemented using a Participatory Action Research (PAR) approach. The program engaged lecturers, students, and group members in stages of socialization, training, technology implementation, mentoring, and sustainability planning. Evaluation results indicated a 12% improvement in participants’ understanding based on pre-test and post-test scores, demonstrating the program’s effectiveness in strengthening technical competence. Technological implementation, including the construction of a seed house and the use of pH and TDS meters, resulted in 1,500 high-quality seedlings and a hydroponic pakcoy harvest of 18.4 kg. Participants successfully applied practical skills independently, particularly in nutrient management and the cultivation of economically valuable crops. The program also fostered an internal training system for new members and generated socio-economic benefits, such as increased household income and strengthened women’s roles in agriculture. Overall, this activity aligns with SDGs 1, 2, 5, and 12.